2010
DOI: 10.1017/s1743921311020047
|View full text |Cite
|
Sign up to set email alerts
|

A possible dividing line between massive planets and brown-dwarf companions

Abstract: Abstract. Brown dwarfs are intermediate objects between planets and stars. The lower end of the brown-dwarf mass range overlaps with the one of massive planets and therefore the distinction between planets and brown-dwarf companions may require to trace the individual formation process. We present results on new potential brown-dwarf companions of Sun-like stars, which were discovered using CORALIE radial-velocity measurements. By combining the spectroscopic orbits and Hipparcos astrometric measurements, we ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
3
7
0
Order By: Relevance
“…−23 MJup, derived by Grether & Lineweaver (2006) using their stellar companion and giant planet sample within 50 pc around the sun. This mass function minimum is also consistent with that derived by Sahlmann et al (2011b), who found a void in the mass range between 25 and 45 MJup using the data from the CORALIE radial-velocity survey. They further suggested that there may be a possible dividing line between massive planets and substellar companions.…”
Section: Two Different Brown Dwarf Populationssupporting
confidence: 91%
See 1 more Smart Citation
“…−23 MJup, derived by Grether & Lineweaver (2006) using their stellar companion and giant planet sample within 50 pc around the sun. This mass function minimum is also consistent with that derived by Sahlmann et al (2011b), who found a void in the mass range between 25 and 45 MJup using the data from the CORALIE radial-velocity survey. They further suggested that there may be a possible dividing line between massive planets and substellar companions.…”
Section: Two Different Brown Dwarf Populationssupporting
confidence: 91%
“…They further suggested that there may be a possible dividing line between massive planets and substellar companions. Schneider et al (2011) has chosen arbitrarily and probably provisionally 25MJup as the upper limit of massive planets based on previous studies (e.g., Sahlmann et al 2011b;Baraffe, Chabrier, & Barman 2010).…”
Section: Two Different Brown Dwarf Populationsmentioning
confidence: 99%
“…Because there was no such minimum in the mass spectrum of free-floating brown dwarfs, they speculated that migration and not a characteristic mass scale of fragmentation in protoplanetary disks was responsible for the apparent minimum. Sahlmann et al (2011) used the combination of the Doppler and astrometric techniques to remove the sin i degeneracy to confirm the previous result, finding that low-mass brown dwarfs with M 25 M Jup cleanly separated from high-mass brown dwarfs with M 45 M Jup . In contrast to Grether & Lineweaver (2006), they argued that the low-mass brown dwarfs may be massive planets formed by core accretion.…”
Section: Comparison To Previous Studies Of Thesupporting
confidence: 62%
“…The choice of 25 M the authors justified by the start of a dip at around this mass in the observed distribution in M sin i of substellar mass objects [e.g. 185,[187][188][189].…”
Section: Very Massive Giants and Metallicitymentioning
confidence: 99%